Real-World Outcomes of Fusion-Directed Targeted Therapy in Advanced Non-Small Cell Lung Cancer Harboring Actionable Gene Fusions - Faure Delgado Leon; Suset Almuinas de Armas; Melanie Molina; Eric G. Morales; Maria Fernandez-Gomez; Luis Estuardo Raez (International Journal of Molecular Sciences, 2026)
Actionable ALK, ROS1, RET, NTRK, and NRG1 fusions define biologically distinct subsets of advanced non-small cell lung cancer (NSCLC), yet real-world data across these rare populations remain limited. We retrospectively evaluated patients with advanced NSCLC treated at Memorial Healthcare System who received genotype-matched fusion-directed therapy; the first fusion-directed agent defined the index treatment, and survival was measured from its initiation. Progression was determined from radiographic reports and treating-oncologist documentation. After patient-level reconciliation, 59 unique patients were included: 29 ALK, 14 ROS1, 11 RET, 3 NTRK, and 2 NRG1. Median follow-up was 47.7 months (95% CI, 28.6–58.7), median progression-free survival was 44.8 months (95% CI, 17.1–not estimable), and median overall survival was not reached. No statistically significant survival differences were detected among ALK, ROS1, and RET subgroups, although limited sample sizes preclude exclusion of clinically meaningful differences. Later-line index therapy was not significantly associated with progression-free survival in exploratory unadjusted analysis. These findings provide descriptive real-world evidence of precision-oncology implementation across actionable fusion-defined NSCLC while underscoring that pooled outcomes should not be interpreted as evidence of equivalent efficacy across molecular subtypes or therapies.